Investigation of the effect of telmisartan on experimentally induced peripheral nerve injury in rats. (1st June 2015) - Yuksel, Tugba Nurcan; Halici, Zekai; Demir, Recep; Cakir, Murteza; Calikoglu, Cagatay; Ozdemir, Gokhan; Unal, Deniz
<x xml:space="preserve">Abstract</x> Aim: The aim of this study was to investigate the effects of telmisartan on nerve healing in a rat peripheral nerve injury model. Material and method: Thirty adult male Wistar albino rats were divided into five groups: healthy, axonotmesis, anastomosis, axonotmesis+10 mg/kg telmisartan and anastomosis+10 mg/kg telmisartan. Walking track analyses were performed 4 weeks after the surgery. The right sciatic nerves of all the animals were exa- mined histopathologically, stereologically and molecularly. Results: Many badly damaged axons were detected in the axonotmesis group, in addition to enlarged spaces between the axons. In the anastomosis group, both ir- regular and degenerated axons at different severities were observed. The sections of the telmisartan group after the axonotmesis were similar to those of the healthy group. The sections of the telmisartan group after the anastomosis were similar to those of the healthy group and the telmisartan group after the axonotmesis. Interleukin-1 beta (IL-1β) gene expression increased in both the axonotmesis and the anastomosis groups when compared with the healthy group. Telmisartan had a significant down-regulatory effect on IL-1β expression. Caspase-3 mRNA expression was significantly increased in the anastomosis group, and the administration of telmisartan in this group significantly decreased this rise in caspase-3 mRNA expression. As a functional outcome, telmisartan also increased the walking distance of the rats after axonotmesis and anastomosis. Conclusion: The histopathological, stereological, functional and molecular data suggest that telmisartan improves nerve regeneration in peripheral nerve injuries by inhibiting inflammatory cytokine IL-1β and apoptotic caspase-3.